Carbazole-based enamine: Low-cost and efficient hole transporting material for perovskite solar cells. (February 2017) - Daskeviciene, Maryte; Paek, Sanghyun; Wang, Zhiping; Malinauskas, Tadas; Jokubauskaite, Gabriele; Rakstys, Kasparas; Cho, Kyung Taek; Magomedov, Artiom; Jankauskas, Vygintas; Ahmad, Shahzada; Snaith, Henry J.; Getautis, Vytautas; et al.
Abstract: A simple carbazole-based conjugated enamineV950 was synthesized, fully characterized and incorporated into a perovskite solar cell, which displayed high power conversion efficiency close to 18%. The investigated hole transporting material was synthesized via an extremely simple route (one step, no expensive catalysts, no column chromatography or sublimation purification) from commercially available and relatively inexpensive starting reagents, resulting in more than one order of magnitude lower cost of the final product compared to the commercial 2, 2′, 7, 7′-tetrakis( N, N -di- p -methoxy-phenylamine)-9-9′-spirobifluorene (spiro-OMeTAD). This material promises to be a viable p-type organic charge conductor to be employed in the scale-up and manufacturing of perovskite solar modules. Graphical abstract: New carbazole-based conjugated enamine small-molecule hole conductor, that yields an overall efficiency of 17.8% in perovskite-based solar cells, was prepared in one step without use of expensive catalysts, column chromatography or sublimation purification. Highlights: Palladium catalyst-free synthesis of HTMs for perovskite solar cells is proposed. One step synthesis procedure and simplified purification offer significant HTM synthesis cost reduction. Effectiveness of V950 as an alternative to the spiro-OMeTAD for a wide range of perovskite materials is evaluated.